Russian Vector in the Formation of a Common Social and Socio-Cultural Space in the South Caucasus - Ekaterina Sergeevna Andreeva; Inna Anatolyevna Orlova (Управленческое консультирование)
The article analyzes the phenomenon of “social space”, reveals the historical role of Russia in the formation of the unified social space on the South Caucasus, examines the doctrinal views of scientists and politicians of the Russian Federation and the Caucasian states on the process of formation social area in the Caucasus, assesses the prospects of the impact of the leading actors of foreign policy on the social space in the South Caucasus.